Suppression of NMDA receptor function in mice prenatally exposed to valproic acid improves social deficits and repetitive behaviors - Kang, Jaeseung; Kim, Eunjoon (Frontiers in Molecular Neuroscience, 2015)
Animals prenatally exposed to valproic acid (VPA), an antiepileptic agent, have been used as a model for autism spectrum disorders (ASDs). Previous studies have identified enhanced NMDA receptor (NMDAR) function in the brain of VPA rats, and demonstrated that pharmacological suppression of NMDAR function normalizes social deficits in these animals. However, whether repetitive behavior, another key feature of ASDs, can be rescued by NMDAR inhibition remains unknown. We report here that memantine, an NMDAR antagonist, administered to VPA mice rescues both social deficits and repetitive behaviors such as self-grooming and jumping. These results suggest that suppression of elevated NMDAR function in VPA animals normalizes repetitive behaviors in addition to social deficits.